The impact of the macroeconomy on health insurance coverage: Evidence from the great recession - John Cawley; Asako S. Moriya; Kosali Simon (Institute for the Study of Labor (IZA), 2011)
This paper investigates the impact of the macroeconomy on the health insurance coverage of Americans using panel data from the Survey of Income and Program Participation (SIPP) for 2004-2010, a period that includes the Great Recession of 2007-09. We find that a one percentage point increase in the state unemployment rate is associated with a 1.67 percentage point (2.12%) reduction in the probability that men have health insurance; this effect is strongest among college-educated, white, and older (50-64 year old) men. We estimate that 9.3 million Americans, the vast majority of whom were adult men, lost health insurance due to a higher unemployment rate alone during the 2007-09 recession. We conclude with a discussion of how components of recent health care reform may influence this relationship in the future.
urn:nbn:de:101:1-201112121717
Keywords: I10; J3; J6; E32; 330; health insurance; Medicaid; SCHIP; recession; unemployment; Gesundheitswesen; Krankenversicherung; Wirtschaftslage; Wirtschaftskrise; USA